A transgenic resource for conditional competitive inhibition of conserved Drosophila microRNAs. - Fulga, T.A.; McNeill, E.M.; Binari, R.; Yelick, J.; Blanche, A.; Booker, M.; Steinkraus, B.R.; Schnall-Levin, M.; Zhao, Y.; DeLuca, T.; Bejarano, F.; Han, Z.; et al. (Nature communications, 2015)
Although the impact of microRNAs (miRNAs) in development and disease is well established, understanding the function of individual miRNAs remains challenging. Development of competitive inhibitor molecules such as miRNA sponges has allowed the community to address individual miRNA function in vivo. However, the application of these loss-of-function strategies has been limited. Here we offer a comprehensive library of 141 conditional miRNA sponges targeting well-conserved miRNAs in Drosophila. Ubiquitous miRNA sponge delivery and consequent systemic miRNA inhibition uncovers a relatively small number of miRNA families underlying viability and gross morphogenesis, with false discovery rates in the 48% range. In contrast, tissue-specific silencing of muscle-enriched miRNAs reveals a surprisingly large number of novel miRNA contributions to the maintenance of adult indirect flight muscle structure and function. A strong correlation between miRNA abundance and physiological relevance is not observed, underscoring the importance of unbiased screens when assessing the contributions of miRNAs to complex biological processes.